Hands-On Computer Vision with TensorFlow 2 : Leverage Deep Learning to Create Powerful Image Processing Apps with TensorFlow 2. 0 and Keras. - Planche, Benjamin (Packt Publishing, Limited, 2019)
Computer vision is achieving a new frontier of capabilities in fields like health, automobile or robotics. This book explores TensorFlow 2, Google's open-source AI framework, and teaches how to leverage deep neural networks for visual tasks. It will help you acquire the insight and skills to be a part of the exciting advances in computer vision.